Seasonal changes in the amount of carbohydrates and photosynthetic activity of Pinus pumila Regal on alpine in central Japan - Kibe, Takeshi; Masuzawa, Takehiro (National Institute of Polar Research, 1992)
P(論文) Branches and needles of Pmus pumila REGEL were collected from a site in the Yatsugatake mountain range in central Japan They were divided into current, 1-year-old, 2-year-old and 3-year-old parts Then, soluble carbohydrate (total sugars and starch) included in each of them was analyzed by SOMOGYI-NELSON method Photosynthetic rate of needles was measured by an infrared CO_2 gas analyzer Total sugar contents of branches and needles showed high levels in the winter season, but starch content levels were low In the younger part, total sugar content showed a higher level than in the older part Net photosynthetic rate of needles was the highest in summer, and was slightly negative in winter. departmental bulletin paper